Plant Defensive β-Glucosidases Resist Digestion and Sustain Activity in the Gut of a Lepidopteran Herbivore - Vassão, Daniel Giddings; Wielsch, Natalie; Gomes, Ana Maria de Melo Moreira; Gebauer-Jung, Steffi; Hupfer, Yvonne; Svatoš, Aleš; Gershenzon, Jonathan (Frontiers in Plant Science, 2018)
Two-component activated chemical defenses are a major part of many plants’ strategies to disrupt herbivory. The activation step is often the β-glucosidase-catalyzed removal of a glucose moiety from a pro-toxin, leading to an unstable and toxic aglycone. While some β-glucosidases have been well studied, several aspects of their roles in vivo, such as their precise sites of enzymatic activity during and after ingestion, and the importance of particular isoforms in plant defense are still not fully understood. Here, plant defensive β-glucosidases from maize, white mustard and almonds were shown to resist digestion by larvae of the generalist lepidopteran Spodoptera littoralis, and the majority of the ingested activities towards both general and plant pro-toxic substrates was recovered in the frass. Among other proteins potentially involved in defense, we identified specific plant β-glucosidases and a maize β-glucosidase aggregating factor in frass from plant-fed insects using proteomic methods. We therefore found that, while S. littoralis larvae efficiently degraded bulk food protein during digestion, β-glucosidases were among a small number of plant defensive proteins that resist insect digestive proteolysis. These enzymes remain intact in the gut lumen and frass and can therefore further catalyze the activation of plant defenses after ingestion, especially in pH-neutral regions of the digestive system. As most of the ingested enzymatic activity persists in the frass, and only particular β-glucosidases were detected via proteomic analyses, our data support the involvement of specific isoforms (maize ZmGlu1 and S. alba MA1 myrosinase) in defense in vivo.